Characterization and In-vitro Study of Micro-encapsulation Chitosan Alginate of Single-bulb Garlic Extract - Lestari, Sri R.; Gofur, Abdul; Hartatiek, Dra.; Annisa, Yuslinda; Ramadhani, Dimas Nur; Rahma, Amalia Nur; Aisyah, Dahniar Nur; Mufidah, Ikfi Nihayatul; Dini Rifqi, Nadiya (Pharmaceutical Nanotechnology, 2024)
> Background: Single-bulb garlic extract (SBGE) contains more active compounds than regular garlic, but it is unstable and easily degraded in the digestive tract. SBGE is expected to be protected by microencapsulation chitosan-alginate (MCA). Objective: The present study aimed to characterize and assess the antioxidant activity, hemocompatibility, and toxicity of MCA-SBGE in 3T3-L1 cells. Methods: The research procedures consist of extraction of single bulb garlic, preparation of MCASBGE, Particle Size Analyzer (PSA), FTIR analysis, DPPH assay, hemocompatibility test, and MTT assay. Results: The average size of MCA-SGBE was 423.7 ± 2.8 nm, the polydispersity index (PdI) was 0.446 ± 0.022, and the zeta potential was -24.5 ± 0.4 mV. MCA-SGBE was spherical with a diameter range of 0.65-0.9 μm. A shift in absorption and addition of functional groups was found in SBGE after encapsulation. MCA-SBGE, at a concentration of 24 x 103 ppm, has higher antioxidants than SBGE. The hemocompatibility test shows the hemolysis of MCA-SBGE lower than SBGE. MCA-SBGE was not toxic to 3T3-L1 cells with cell viability percentage above 100% at all concentrations. Conclusion: MCA-SBGE characterization has microparticle criteria with homogeneous PdI values, low particle stability, and spherical morphology. The results showed that SBGE and MCA-SBGE are nonhemolytic, compatible with red blood cells, and non-toxic to 3T3-L1 cells.
Keywords: hemocompatibility test